2017
DOI: 10.1088/1751-8121/aa71c1
|View full text |Cite
|
Sign up to set email alerts
|

Record statistics of a strongly correlated time series: random walks and Lévy flights

Abstract: Abstract. We review recent advances on the record statistics of strongly correlated time series, whose entries denote the positions of a random walk or a Lévy flight on a line. After a brief survey of the theory of records for independent and identically distributed random variables, we focus on random walks. During the last few years, it was indeed realized that random walks are a very useful "laboratory" to test the effects of correlations on the record statistics. We start with the simple one-dimensional ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
132
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(137 citation statements)
references
References 156 publications
(707 reference statements)
5
132
0
Order By: Relevance
“…For any symmetric jump distribution, one obtains the behavior Q n ∼ n −1/2 for large n, independently of the distribution itself. It can be shown that such a decay also holds for walks with nearest-neighbor jumps, i.e., a particular case of non-continuous jump distribution, provided that the jumps are symmetric, independent and identically distributed [32]. Therefore, in the paradigmatic case of the simple symmetric random walk on the integers, one finds that the value 1 2 describes the powerlaw decay of the survival probability and gives the correct parameter describing both the Lamperti and the Mittag-Leffler distributions.…”
Section: Decay Of the Survival Probabilitymentioning
confidence: 99%
“…For any symmetric jump distribution, one obtains the behavior Q n ∼ n −1/2 for large n, independently of the distribution itself. It can be shown that such a decay also holds for walks with nearest-neighbor jumps, i.e., a particular case of non-continuous jump distribution, provided that the jumps are symmetric, independent and identically distributed [32]. Therefore, in the paradigmatic case of the simple symmetric random walk on the integers, one finds that the value 1 2 describes the powerlaw decay of the survival probability and gives the correct parameter describing both the Lamperti and the Mittag-Leffler distributions.…”
Section: Decay Of the Survival Probabilitymentioning
confidence: 99%
“…Using Eqs. (17), (18) and (25) together with the fact that inf I is negligible compared to E max (t), we get…”
Section: Equilibrium Regimementioning
confidence: 93%
“…In this regime Eqs. (17) and (18) still hold, whereas Eq. (7) fails, making E min (t) irrelevant for the calculation of E max (t).…”
Section: Equilibrium Regimementioning
confidence: 99%
“…. , I n are statistically independent [2,3,10]. The distribution of M n ensues from this fact by elementary considerations (see also section 7.4 below).…”
Section: Introductionmentioning
confidence: 99%